The Effectiveness of the Method Chiva in Patients with Chronic Venous Insufficiency and Comorbid Lesions: own Experience - Yarka A. (Львівський клінічний вісник)
Introduction. Chronic venous insufficiency (CVI) of the lower extremities is one of the most popular topics both in vascular surgery and the entire practice of medicine. A particular problem arises when it comes to the choice of treatment of CVI in patients with comorbid lesions. Some authors consider it expedient to apply a compression technique for the treatment of patients with comorbid lesions, but life-long use of it has certain disadvantages. This is also indicated by the latest consensus on the treatment of CVI, where the CHIVA method is distinguished as quite effective, but not widely used. The aim of the study was to examine the effectiveness of the method CHIVA in patients with comorbidities. Materials and methods. In the period from 2011 to 2015 were treated 37 patients with CVI, the selected treatment was CHIVA. The average age of patients was 78 years. Operations were carried out under the local anesthesia. Results and discussion. In all the patients there was observed a regression of signs of CVI. 23 (62.1 %) patients achieved a stable cosmetic effect when observed for 3 years. In the postoperative period the recurrent bleeding from varicose nodes was not observed in any of the patients. Paresthesia in the cut places was observed in 14 (37.8 %) patients, subcutaneous hematomas were observed in 3 (8.1 %) patients. The thrombosis of saphenous veins without signs of inflammation were found by the control ultrasound examination in 11 (29.7 %) patients. Thrombosis of the deep venous system were not observed. In patients with concomitant diseases the systemic complications and exacerbations of the main chronic diseases in the early postoperative period were not observed. By applying the CHIVA surgery procedure, we did not try to achieve a quick cosmetic effect, as is the case with the use of classical methods of surgery and other non-invasive interventions. The goal of CHIVA’s low-invasive operations is to achieve a reduction in pressure in the superficial venous system, which is the main pathogenetic mechanism of occurrence of CVI and causes undesirable consequences of this disease. Transversal venous outflow from the source of pathological reflux allows you to achieve the goal. According to our study, the overwhelming majority of patients treated with CHIVA were elderly and had severe comorbid lesions, which posed a risk for the use of a classic surgical intervention in the presence of CVI. In some patients, deformation of the trunk of the large subcutaneous vein and its mouth, as well as pronounced dilation, did not allow for endovascular laser or radiofrequency ablation. Operative treatment was needed because of the presence of severe forms of CWI and its complications. The use of local anesthesia also had a positive effect, since it minimized the medication effect on the body, made it possible to maximally reduce the length of stay of the patient in the hospital. The average length of stay of a patient in a hospital of 1,2 days minimized the occurrence of such a phenomenon as a hospital pneumonia Conclusions. Using the method CHIVA therapy in the treatment of chronic venous insufficiency is a safe and effective method and can be used in patients with comorbidities.